2007
DOI: 10.1007/s10633-007-9101-x
|View full text |Cite
|
Sign up to set email alerts
|

Photopic ON- and OFF-responses in complete type of congenital stationary night blindness in relation to stimulus intensity

Abstract: The complete type of congenital stationary night blindness (complete CSNB) is a retinal disorder where the ON-response b-wave of the photopic electroretinogram is reduced, while the ON-response a-wave and OFF-response d-wave are preserved. These findings are related to ON-bipolar cell dysfunction, whereas the effects of myopia, which is usually associated with complete CSNB, have not been studied yet. The aim was to investigate ON-bipolar cell dysfunction in complete CSNB with variable-intensity stimuli, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…For example, the b-wave is either eliminated or reduced more than the d-wave in certain retinal diseases, including congenital stationary night blindness [27,[31][32][33][34][35], malignant melanoma associated retinopathy [9,36,37], x-linked retinoschisis [17,38,39] x-linked retinitis pigmentosa [26] and phosphomannomutase deficiency [40]. Conditions in which the ERG d-wave is more reduced than the b-wave have been reported in few cases, but which had uncertain underlying etiology [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the b-wave is either eliminated or reduced more than the d-wave in certain retinal diseases, including congenital stationary night blindness [27,[31][32][33][34][35], malignant melanoma associated retinopathy [9,36,37], x-linked retinoschisis [17,38,39] x-linked retinitis pigmentosa [26] and phosphomannomutase deficiency [40]. Conditions in which the ERG d-wave is more reduced than the b-wave have been reported in few cases, but which had uncertain underlying etiology [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…The recording electrode (HK-loop 5 ) was hooked to the lower lid as previously reported elsewhere. 6,7 The reference and ground electrodes (Grass silver cup electrodes; Grass Technologies, West Warwick, RI) were pasted at the level of the external canthus and on the forehead, respectively. The pupils were maximally dilated with 1% tropicamide (Mydriacyl; Alcon, Inc., Fort Worth, TX).…”
Section: Methodsmentioning
confidence: 99%
“…All significant results after correction for multiple testing are included. Observe the inverse scaling for the amplitudes of the a-wave and the PhNR on however, indicated that the PhNR can be attributed to activity in the inner retinal layers [7], [10], [18], [20][21][22][23], suggesting that the fullfield ERG can be of importance in glaucoma diagnosis. Stimulation in those studies was obtained with monitors, fullfield systems or specific LED set-ups.…”
Section: Phnr In Glaucoma Diagnosismentioning
confidence: 99%
“…The white light as used in our measurements could be an explanation for the observation in our study that the diagnostic value of the PhNR off is higher than the one of the PhNR on . More studies in different patient groups [22] are necessary to investigate the diagnostic utility of the long-flash ERG with white and colour stimulation.…”
Section: Phnr With White and Colour Stimulimentioning
confidence: 99%